How agricultural research affects urban poverty in developing countries: the case of China - Fan, Shenggen; Fang, Cheng; Zhang, Xiaobo (International Food Policy Research Institute, 2001)
This paper develops a framework to measure the impact of agricultural research on urban poverty. Increased investments in agricultural R&D can lower food prices by increasing food production, and lower food prices benefit the urban poor because they often spend more than 60% of their income on food. Application of the framework to China shows that these food price effects are large and that the benefits for the urban poor have been about as large as the benefits for the rural poor.